Alcohol Septal Ablation in Patients with Hypertrophic Cardiomyopathy and Obesity - K. V. Rudenko; L. O. Nevmerzhytska; O. Yu. Dudnyk; S. M. Fanta; V. I. Malaniuk; V. V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2019)
The article represents a literature review and analysis of actual experience of the treatment of patients with hypertrophic cardiomyopathy (HCM) and obesity. Obesity is a significant risk factor for the development and course of cardiovascular diseases. There are a lot of articles describing the “obesity paradox” as more favorable prognosis in patients with overweight and obesity compared to those with normal BMI. It refers to a lower level of hospital mortality and mortality in long-term follow-up after percutaneous interventions and open heart surgery. However, these findings are not reliable, since they do not take into account the presence of comorbid and concomitant conditions in patients, have specific criteria for patient selection for the study and use only BMI for the classification of overweight. This reflects the reciprocal causality: weight loss is the result of a serious illness, not its cause.It has been shown that obesity in patients with HCM is associated with a higher left ventricle myocardial mass, more severe symptoms, lower exercise tolerance, and labile obstructive hemodynamics. We studied the effect of obesity on the results of alcohol septal ablation (ASA) in patients with HCM.Obesity is an important risk factor for the development of cardiovascular diseases and is also able to affect cardiac surgery risks. It has been shown that ASA in patients with HCM and obesity in most cases may improve clinical course of the disease (symptoms and functional class improvement). Also, there is no difference in the anatomical and hemodynamic results, mortality rate in obese patients and those with normal BMI in the immediate follow-up. ASA is recommended as a first-line method in patients with HCM and obesity.